BIBLOMETRIC ANALYSIS OF SAVING AND INVESTMENT IN INDIAN CONTEXT - Nishtha Jain, Mukesh Sharma (Journal of Informatics Education and Research, 2025)
India's social and economic structure is changing quickly, and this is reflected in the way people live and behave.[2] These days, people's saving and investing habits are also being impacted by shifting family structures, the allure of international investments or goods, and new governmental regulations. The investment and savings habits of both individual and institutional investors are investigated in this bibliometric investigation. The study investigates how these trends are shaped by socioeconomic factors, including family structure, inflation, income inequality, technology advancements, and governmental regulations.[1] Giving a general overview of saving and investing practices in the Indian setting is the goal of this bibliometric analysis. India's investing and savings habits have changed significantly during the past few decades.[3] This bibliometric analysis's primary goal is to track these developments.